PENGUJIAN METODE LINE BALANCING TERHADAP PRODUKTIVITAS DAN WAKTU TUNGGU PADA LINE SEWING PADA PT BATAM BERSATU APPAREL - Tambunan, Putra Halomoan; Zetli, Sri (LPPM Universitas Putera Batam, 2020)
PT Batam Bersatu Apparel is a one company engaged in garment process and based in Batam city, where is production process are supervised by the leader of sewing line. The sewing process is a second process after the cutting process, in this process cut pieces from cutting department to processing become a clothes after sewing process, the one of problem is extremly happen in the sewing line is a idle time problem in the production process and the effect from this problem is un efficient that line production. The purpose of the research is calculate the line efficiency and also calculate the balance delay in line production with calculate the standard time for the first. And result from this research get for all process which is obras process is 2,11 second jarum satu process 15,22 second and jarum dua process is 12,13 second and standard time in sewing line as big as 40,5925 second and also increase line efficiency from 12,92 go up 19,89 and also get balance delay as big as 7,18 second Keyword: Garment; Line efficiency; Balance delay;Standard time; Cycle time